Students’ Response on Mini Lecture (Cermin) Program on the Learning Intensity in Islamic Education - Rahayu, Santi (Interdisciplinary Social Studies, 2021)
In the current era of globalization, education is very important. If the education of a society develops well, then it is undeniable that the community will be more "qualified" and able to compete against competition that is getting tighter and tighter in various aspects of life activities. In such situations and conditions, "quality" human resources can face competition in life activities. This study aims to find out student responses about Mini Lectures (Cermin) by class II Mekar Arum High School Bandung, knowing the learning intensity of class II SMA Mekar Arum Bandung in the field of Islamic Education studies, and knowing the relationship between class II responses to Cemrin with the intensity of their learning in the field of study of Islamic Education. In general this research uses descriptive method, that descriptive inquiry aims at solving problems that exist in the present. Meanwhile the problems examined by the incident took place in the present and this research intends to reveal actual things. The results showed that students' etiquette towards teachers are students must always respect the teacher and the teacher's family, protect the rights of the teacher, do not walk in front of the teacher, do not sit in the teacher's place, do not start a conversation without the teacher’s permission, do not ask something when the teacher is bored, be on time, do not knock on the door of the teacher's house but be patient waiting for the teacher to come out.